Gender perception of the mathematics teachers towards the usage of media materials in teaching mathematics - Raman, Arumugam; Veloo, Arsaythamby (DonEl Learning Inc, 2012)
The purpose of this study is to identify the relationship between the variables of teacher’s perception towards the usage of media materials in teaching mathematics in State of Perlis secondary schools.This study also identifies the differences in teachers’ perception based on gender.A total of 181 mathematics teacher were involved as the respondents which consist of 71 (40%) male and 110 (60%) female teachers.The data was collected through questionnaires and analyzed using SPSS version 12. The results of the study reveal that a positive significant relationship between the skill variables, facilities provided, effective usage of media materials, and problems faced.The results how a negative significant relationship between the skill variables, problems faced, and effectiveness of the usage of media materials. The results of the study also indicate that there is a significant difference in perception between male and female teachers towards the use of media material in teaching mathematics. The male teachers’ perception is higher than female teachers.Through the findings, it is clear that the use of media materials is important in the teaching of mathematics.Nevertheless, good planning is needed prior to using the media materials, these materials must be used appropriately, and be relevant to the subject matter. In this way, the teaching of mathematics in the secondary schools can be more effective and efficient.